2007
DOI: 10.1095/biolreprod.106.059626
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aspects of the Sperm-Associated Antigen 11 (SPAG11) Gene Organization and Expression in Cattle (Bos taurus)1

Abstract: Beta-defensins are small cationic peptides exhibiting broad spectrum antimicrobial properties. In humans, many beta-defensin genes are located within a cluster on chromosome 8p23. The sperm associated antigen 11 (SPAG11) gene is contained in this cluster and is unusual among the human beta-defensins due to its complex genomic structure and mRNA splicing pattern. Here we report the genomic organization of the Bos taurus SPAG11 gene located on chromosome 27q1.2, within a cluster of beta-defensin genes. The exon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…In human testes, immunoreactive β-defensin-1 was localized in the Leydig cells and early and elongated spermatids, whereas discrete immunolabeling occurred in pachytene spermatids (Com et al, 2003). Sperm associated antigen II (SPAG II), the gene of which is included in the β-defensin cluster, was immunolocalized in late stage spermatids and in Sertoli cells in cattle testes (Avellar et al, 2007). Therefore, it is suggested that late stage of spermatids produce AvBD-3 in the chicken testes as some of the mammalian spermatids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human testes, immunoreactive β-defensin-1 was localized in the Leydig cells and early and elongated spermatids, whereas discrete immunolabeling occurred in pachytene spermatids (Com et al, 2003). Sperm associated antigen II (SPAG II), the gene of which is included in the β-defensin cluster, was immunolocalized in late stage spermatids and in Sertoli cells in cattle testes (Avellar et al, 2007). Therefore, it is suggested that late stage of spermatids produce AvBD-3 in the chicken testes as some of the mammalian spermatids.…”
Section: Discussionmentioning
confidence: 99%
“…These defensins may play roles not only in innate immunity but also in male fertility, sperm survival in male reproductive tract, and sperm-egg interaction in mammals (Com et al, 2003;Palladino et al, 2003;Yudin et al, 2003;Zhou et al, 2004). Sperm associated antigen (SPAG11), known as epididymal protein 2 (EP2) in monkey, human epididymis 2 (HE2), and rat spag 11, are antimicrobial peptides attached on the sperm surface (Hamil et al, 2000;Yenugu et al, 2004Yenugu et al, , 2006aAvellar et al, 2007). It has not been reported whether avian sperm express antimicrobial peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The conserved R 60 [1,5] site of cleavage by TPSAB1 and prohormone convertase suggests an important function. Cleavage at R 60 was suggested to activate SPAG11B/D [48,49] similar to the tightly regulated cleavage activation of alphadefensin human defensin 5 [54] and other defensins [55].…”
Section: Discussionmentioning
confidence: 99%
“…Human spermatozoa were fixed and stained as previously described [5]. Surplus swim-up spermatozoa were obtained after approval by the University of North Carolina at Chapel Hill Human Subjects Committee and with informed consent and were provided by the Assisted Reproductive Technology Clinic, University of North Carolina at Chapel Hill.…”
Section: Immunohistochemical Localizationmentioning
confidence: 99%
See 1 more Smart Citation